Movement-Integrated Learning and Students’ Learning Focus in Mathematics: A Single-Subject Study - wulandari, Yiyin; Damayanti, Nia Wahyu (FKIP Universitas Wisnuwardhana, 2026)
Learning focus plays a fundamental role in mathematics achievement, particularly in topics requiring sustained attention and symbolic reasoning, such as Single Variable Linear Equations (SVLE). Despite growing evidence on the benefits of physical activity for attention, research on Movement-Integrated Learning in mathematics through a single-subject design remains limited. This study aims to examine how Movement-Integrated Learning influences the learning focus of a student with high physical activity characteristics during SVLE instruction. A qualitative A-B single-subject research (SSR) design was employed with one seventh-grade student selected through purposive sampling. Three instruments were used: a focus observation sheet measuring on-task and off-task behavior at five-minute intervals, field notes documenting learning context, and semi-structured interviews exploring the students' experiences. Data were collected across a baseline phase of three conventional sessions and an intervention phase of five movement-integrated sessions. Analysis followed a qualitative framework of data reduction, presentation, and conclusion drawing, with SSR between-condition analysis examining changes in level, trend, stability, and phase overlap, validated through triangulation. The baseline phase showed fluctuating and declining attention patterns with limited focus endurance. The intervention phase demonstrated an upward trend in focus scores, greater stability, extended attention duration, and no phase overlap, indicating a functional relationship between structured movement and improved attentional regulation. These findings suggest that when deliberately integrated into instructional design, movement serves as a regulatory mechanism supporting sustained cognitive engagement for students with high motor activity characteristics.